PENGARUH PROFITABILITAS, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG - Humaira Rania Budisisworo, (2023)
The purpose of this study is to examine and analyze the effect of Profitability, Solvability, and Company Size on Audit Report Lag. By using a purposive sampling technique as a sample collection technique, 610 sample were generated from 122 manufacturing sector companies listed on the Indonesia Stock Exchange during the 2017 - 2021 period. Multiplier linier regression analysis is a data analysis technique used with panel data regression using STATA 16 software. The results showed that the profitability has a negative effect on audit report lag and company size has effect on audit report lag. However, solvability has no effect on audit report lag.